IMPLEMENTATION OF ELECTRONIC TRAFFIC LAW ENFORCEMENT SYSTEM IN RESOLVING TRAFFIC VIOLATION CRIMES TO IMPROVE LEGAL ORDER (Case Study at Grobogan Police) - Satria, Moh. Pandu Putra; Hafidz, Jawade (UNISSULA Semarang, 2024)
The purpose of this research: 1). To study and analyze the implementation of the Electronic Traffic Law Enforcement system in resolving criminal acts of traffic violations to improve legal order at the Grobogan Police; 2). To study and analyze the obstacles to the implementation of the Electronic Traffic Law Enforcement system in resolving criminal acts of traffic violations to improve legal order at the Grobogan Police and its solutions. This research uses an empirical legal approach, with a descriptive analytical research method. The data used are primary and secondary data which will be analyzed qualitatively. The research problems are analyzed using Lawrence Friedman's legal system theory and the theory of legal effectiveness. The results of the study concluded that: 1) The implementation of the E-Tilang system in resolving criminal acts of traffic violations has been guided by Law Number 29 of 2009 concerning Traffic and Road Transportation, the flow is when the police have issued a manual ticket (writing on the ticket form), then the police then enter the data back into the E-Tilang application, the E-Tilang server will automatically send a notification of the amount of fine deposit that can be paid at the bank along with the article violated by the violator. After paying the fine deposit (not yet sentenced) then the evidence of the ticket can be exchanged for the fine deposit; 2). The obstacles in the implementation of the Electronic Traffic Law Enforcement system in resolving criminal acts of Traffic violations in Grobogan are as follows: a). Law Enforcement Factors, in this case law enforcers are law enforcement officers who usually in carrying out their duties and functions there are errors in the input application that make officers lose track of the violator; b). Facilities and Infrastructure Factors, in the implementation of Electronic Traffic Law Enforcement in the jurisdiction of Grobogan Regency, it is recorded that there are only 2 CCTV units; c). Community Factors, Poor social behavior in traffic is one of the problems that has been rampant in Indonesia since the past until now.